Domestic impact of the African Charter Human and Peoples' Rights and the protocol on the rights of woman in Africa : a case study of Nigeria - Akonumbo, Atangcho Nji (University of Pretoria, 2012)
Thesis (LLM (Human Rights and Democratisation in Africa))--University of Pretoria, 2011.